P9 Nintedanib for the treatment of Idiopathic Pulmonary Fibrosis – initial clinical experience in a UK cohort. (12th November 2015) - Fletcher, SV; Jones, MG; Renzoni, E; Parfrey, H; Hoyles, R; Spinks, K; Kokosi, M; Kwok, A; Warburton, C; Titmuss, V; Maher, T; Chua, F; et al.
Abstract : Introduction and objectives: Nintedanib (OFEV®) is the second drug licensed for the treatment of Idiopathic Pulmonary Fibrosis (IPF). Evidence from the INPULSIS study demonstrated that it reduced annual FVC decline by approximately 50%. Nintedanib has been available in the UK from October 2014 through the Individual Patient Supply Programme (IPSP); initially for those with FVC >50% predicted, latterly available for all with a diagnosis of IPF regardless of FVC. We present preliminary findings of clinical experience with nintedanib in routine UK clinical practice. Methods: A multi-centre, cohort review was undertaken across 6 NHS Trusts. Data were collected from clinical records of individuals receiving nintedanib for the treatment of IPF from October 2014 to July 2015. Results: 210 patients (161 male) had consented to nintedanib IPSP by July 2015. Mean age (±S. D.) at diagnosis was 70.0 ± 7.7 years. Reasons for starting nintedanib included ineligibility for pirfenidone (FVC >80% predicted: 67 (31.9%) and FVC <50% predicted: 12 (5.7%)), intolerance to pirfenidone 63 (30%), patient preference 54 (25.7%), and clinical progression on pirfenidone 8 (3.8%). Pre-treatment lung function was FVC 72.2 ± 19.0% and DLCO 40.1 ± 17.2% predicted (Domiciliary oxygen was administered to 66 (31.4%) of the cohort. Mean duration of treatment was 2.4 months (range 0 – 8 months) and 78 patients had completed 3-month follow up. Of these 14/78 patients (17.9%) had discontinued nintedanib due to diarrhoea (5 patients), other GI side effects (3), death/lung transplant (2/1), miscellaneous reasons (3). The commonest potential adverse drug reaction (ADR) was diarrhoea occurring in 21/78 (26.9%), which required a dose reduction in 11 patients. Other common ADRs included nausea 11/78 (14.1%), abdominal pain 11/78 (14.1%), decreased appetite 7/78 (9.0%), and weight loss 5/78 (6.4%). Conclusions: These data demonstrate that at 3 months follow up, Nintedanib is generally well tolerated when used in routine UK practice in patients with IPF across a wide range of FVC's. The incidence of diarrhoea at 3 months is much lower than the 12 month reported rate in the INPULSIS study. Ongoing longitudinal follow up of this cohort will further inform our understanding of the use of nintedanib for the treatment of IPF.